Video-Rate Bioluminescence Imaging of Degranulation of Mast Cells Attached to the Extracellular Matrix - Yokawa, Satoru; Suzuki, Takahiro; Hayashi, Ayumi; Inouye, Satoshi; Inoh, Yoshikazu; Furuno, Tadahide (Frontiers in Cell and Developmental Biology, 2018)
Degranulation refers to the secretion of inflammatory mediators, such as histamine, serotonin, and proteases, that are stored within the granules of mast cells and that trigger allergic reactions. The amount of these released mediators has been measured biochemically using cell mass. To investigate degranulation in living single cells, fluorescence microscopy has traditionally been used to observe the disappearance of granules and the appearance of these discharged granules within the plasma membrane by membrane fusion and the movement of granules inside the cells. Here, we developed a method of video-rate bioluminescence imaging to directly detect degranulation from a single mast cell by measuring luminescence activity derived from the enzymatic reaction between Gaussia luciferase (GLase) and its substrate coelenterazine. The neuropeptide Y (NPY), which was reported to colocalize with serotonin in the secretory granules, fused to GLase (NPY-GLase) was efficiently expressed in rat basophilic leukemia (RBL-2H3) cells, a mast-cell line, using a preferred human codon-optimized gene. Bioluminescence imaging analysis of RBL-2H3 cells expressing NPY-GLase and adhered on a glass-bottomed dish showed that the luminescence signals from the resting cells were negligible, while the luminescence signals of the secreted NPY-GLase were repeatedly detected after the addition of an antigen. In addition, this imaging method was applicable for observing degranulation in RBL-2H3 cells that adhered to the extracellular matrix (ECM). These results indicated that video-rate bioluminescence imaging using GLase will be a useful tool for spatiotemporal analysis of degranulation in single mast cells adhered to a variety of ECM.